Prevalence of drug‐related problems associated with direct oral anticoagulants in hospitalized patients: a multicenter, cross‐sectional study. (24th October 2016) - Viprey, M.; Jeannin, R.; Piriou, V.; Chevalier, P.; Michel, C.; Aulagner, G.; Berthiller, J.; Armoiry, X.
Summary: What is known and objective: The complex dose regimens of the direct‐acting oral anticoagulants (DOAC) make their appropriate prescribing highly challenging. Inappropriate prescribing of the DOAC remains poorly addressed. We studied the patterns of DOAC prescription and estimated the prevalence of drug‐related problems (DRPs) associated with their use. Methods: A cross‐sectional study was conducted using data from medical records system of the Lyon teaching hospitals. DRPs, identified among patients who received a DOAC, between 1 January 2010 and 31 July 2013, were categorized according to the Pharmaceutical Care Network Europe Classification System. The prevalence of hospital stays with a DRP was estimated, and a subgroup analysis according to DOAC and their indication for use was provided. Clinical outcomes were not assessed. Results: Of the 4154 hospital stays with at least one DOAC administration [3412 patients; median age (range): 71 years (14–98), 57% female], 70·8% were excluded from the analysis mainly due to missing information for renal function and/or patient weight. Of the 1188 hospital stays that were screened, 100 DRPs were identified (prevalence 8·4%; 95% CI, 6·8–10·0). The highest prevalence was found among patients who received rivaroxaban for atrial fibrillation (14·6%; 95% CI, 10·7–18·5). A too low drug dose was the most frequent DRP ( n  =   56; 4·7%), followed by a too high drug dose ( n  =   37; 3·1%), contraindication ( n  =   5; 0·4%), and pharmacokinetic problem requiring dose adjustment ( n  =   2; 0·2%). What is new and conclusion: Drug‐related problems associated with the DOACs occur quite commonly among hospitalized patients. Although these DRPs were considered to be of minor severity, prescribing protocols to support better prescribing should be disseminated to reduce the risk to patients. Renal function and body weight data should be mandatory on prescriptions to allow cross‐checking. Abstract : Study flow chart of the selected population on whom the conformity of DOAC prescription was analysed.